POWER RELATIONS AND SEXUAL VIOLENCE IN ISLAMIC BOARDING SCHOOL: ASSESSING CHILD PROTECTION SYSTEMS IN RELIGIOUS EDUCATION INSTITUTIONS IN INDONESIA - Fauzi, Muhammad Alif; Purwanti, Ani; Mahfud , Muh. Afif (Revista Direito e Sexualidade, 2025)
This study investigates sexual violence against children in Islamic boarding schools (pondok pesantren) in Semarang City, aiming to identify the social, cultural, and structural factors that enable such abuse, as well as to evaluate prevention and response efforts by relevant authorities. Guided by a non-doctrinal socio-legal and descriptive-analytical framework, the research draws on primary data from semi-structured interviews with the Head of the Women’s and Children’s Protection Division at the Department of Women’s Empowerment and Child Protection and the Head of Diniyah and Pondok Pesantren Education at the Semarang Ministry of Religious Affairs, supplemented by on-site observations at selected pesantren. Secondary sources include national legislation, institutional guidelines, academic publications, and official reports. Using purposive sampling to engage key stakeholders, qualitative data were analyzed inductively through data reduction, presentation of findings in matrices and charts, and iterative peer-verified conclusion drawing. Findings indicate that sexual violence in pesantren is largely driven by hierarchical power imbalances between caregivers and students, insufficient institutional oversight, and a closed organizational culture that discourages reporting. The Department of Women’s Empowerment and Child Protection plays a critical yet resource-constrained role in victim support and abuse prevention. The study underscores the necessity of comprehensive children’s rights education, enhanced internal supervision mechanisms, and robust policy reforms to strengthen safeguarding measures. These recommendations are intended to inform policymakers, educational leaders, and community stakeholders in fostering a transparent, child-safe environment that supports both the moral and intellectual development of pesantren students.